Nanofabrication of mechano-bactericidal surfaces. Issue 43 (30th October 2017) - Linklater, Denver P.; Juodkazis, Saulius; Ivanova, Elena P.
Abstract : The search for alternatives to standard methods of preventing bacterial adhesion and biofilm formation on biotic and abiotic surfaces alike has led to the use of biomimetics to reinvent, through nanofabrication methods, surfaces whereby the nanostructured topography is directly responsible for bacterial inactivation through physico-mechanical means. Abstract : The search for alternatives to the standard methods of preventing bacterial adhesion and biofilm formation on biotic and abiotic surfaces alike has led to the use of biomimetics to reinvent through nanofabrication methods, surfaces, whereby the nanostructured topography is directly responsible for bacterial inactivation through physico-mechanical means. Plant leaves, insect wings, and animal skin have been used to inspire the fabrication of synthetic high-aspect-ratio nanopillared surfaces, which can resist bacterial colonisation. The adaptation of bacteria to survive in the presence of antibiotics and their ability to form biofilms on conventional antibacterial surfaces has led to an increase in persistent infections caused by resistant strains of bacteria. This presents a worldwide health epidemic that can only be mitigated through the search for a new generation of biomaterials.